Violência doméstica e educação em debate à luz dos processos judiciais da Comarca de Cascavel - Paraná (2018-2020) - Aymoré, Jorge Alexandre Bueno (2024)
Contemporary society has made substantial progress in passing protective laws. However, the number of cases of violence against women has increased over the last five years. Given this, this research aimed to analyze 2,156 digital cases of domestic violence and bodily injury registered with the Paraná State Court of Justice, which occurred in the district of Cascavel - PR, during the years 2018, 2019, and 2020. The investigation was carried out to understand the characteristics of the victims and how the cases were attended to and forwarded, verifying the relationship between these elements and the outcomes of the cases. To this end, far from focusing on individual issues and/or the internal structure of the state system, based on the historical and social foundations of violence and Brazilian laws, the aim was to analyze how judicial proceedings were handled and referred, as well as the relationship between the characteristics of the victims and the outcomes of the proceedings. To this end, bibliographical, documentary, and field research was carried out. Firstly, an attempt was made to understand the historical foundations of domestic violence and defense mechanisms. Then, based on Brazilian legislation and regulatory documents, we looked at how state agencies provide care and operate. Through the application of a questionnaire to the officials who assist the victims and the collection of data from the cases, using descriptive statistics, the relationship between the victim's level of education and financial status and the development of the cases was examined. The research indicated that, of the cases related to bodily injury that took place in the District of Cascavel - PR between 2018 and 2020, only 14% resulted in a conviction, 43.7% were filed, 33.4% were ongoing and 8.9% were acquitted. In all of these outcomes, the majority of the victims reported having completed high school and an income of one minimum wage, and these characteristics were predominant among the victims. The research revealed that the characteristics of the victims do not directly interfere with the outcome of the case, however, given the number of cases filed and in progress, it can be highlighted that there are problems in proving the crime. Another finding is that of the five Criminal Courts in the district, the Domestic Violence Court received five times as many cases as the others, but with the same number of staff, it is similar, revealing the work overload. Finally, it can be concluded that the laws protecting women in Brazil still come up against the strong presence of macho culture and the lack of infrastructure to protect and respond to victims' requests. These are two issues that require public investment, but the immediate need is education to raise awareness about domestic violence, including how to seek state assistance.